2011
DOI: 10.1095/biolreprod.110.088120
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Estrogen and Progesterone on Blood Glutamate Levels: Evidence from Changes of Blood Glutamate Levels During the Menstrual Cycle in Women

Abstract: The gonadal steroids estrogen and progesterone have been shown to have neuroprotective properties against various neurodegenerative conditions. Excessive concentrations of glutamate have been found to exert neurotoxic properties. We hypothesize that estrogen and progesterone provide neuroprotection by the autoregulation of blood and brain glutamate levels. Venous blood samples (10 ml) were taken from 31 men and 45 women to determine blood glutamate, estrogen, progesterone, glucose, glutamate-pyruvate transamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 59 publications
(105 reference statements)
2
29
0
Order By: Relevance
“…Therefore, to reduce glutamate neurotoxicity, it was suggested that we regulate the levels of glutamate in the cerebrospinal fluid (CSF) and ECF by use of familiar mechanisms of glutamate transport from the brain to the blood. In our laboratory, we previously examined various mechanisms to lower glutamate levels including by activation of β 2 -adrenergic receptors and different kinds of hormones [21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to reduce glutamate neurotoxicity, it was suggested that we regulate the levels of glutamate in the cerebrospinal fluid (CSF) and ECF by use of familiar mechanisms of glutamate transport from the brain to the blood. In our laboratory, we previously examined various mechanisms to lower glutamate levels including by activation of β 2 -adrenergic receptors and different kinds of hormones [21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies done by our group and others have shown that pharmacologically reducing blood glutamate levels with glutamate scavengers (such as oxaloacetate and pyruvate) limit glutamate neurotoxicity and provide better neurologic outcomes after various brain insults, particularly traumatic brain injury [14,[19][20][21][44][45][46][47][48][49][50][51][52][53]. Unfortunately, although these treatments have been shown to be effective in animal models of stroke, traumatic brain injury, and subarachnoid hemorrhage, their use in humans is limited by Food and Drug administration restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, on days of the menstrual cycle when blood glutamate levels are at their lowest, plasma estrogen levels are at their highest and vice versa, indicating a potential protective role. 18 It has also been speculated that estrogens may promote venous sinus thrombosis, impairing CSF resorption however, in the current study, subjects with cerebral venous thrombosis were excluded from analysis and we are unable to comment on this association. 19,20 Future studies are needed to further examine the role of progestin only contraceptives with PTCS, other than case studies.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, we have shown in a healthy human population that women have lower blood glutamate concentrations, which fluctuate along the menstrual cycle, inversely correlating with circulating estrogen and progesterone levels [21]. We postulated that this phenomenon is a result of the effect of estrogen and probably progesterone.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent screening of a human population sample, we revealed that gender is an independent factor influencing blood glutamate, which was found to be decreased in females. Along the menstrual cycle, blood glutamate concentrations fluctuated, inversely correlating with estrogen levels [21,22]. However, the precise mechanism of estrogen-induced neuroprotection remains unclear and warrants further studies aimed at determining the role of glutamate-lowering effect in estrogen-induced neuroprotection.…”
Section: Introductionmentioning
confidence: 99%